The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21218253
|View full text |Cite
|
Sign up to set email alerts
|

Morin Hydrate Sensitizes Hepatoma Cells and Xenograft Tumor towards Cisplatin by Downregulating PARP-1-HMGB1 Mediated Autophagy

Abstract: The cross-talk between apoptosis and autophagy influences anticancer drug sensitivity and cellular death in various cancer cell lines. However, the fundamental mechanisms behind this phenomenon are still unidentified. We demonstrated anti-cancerous role of cisplatin (CP) and morin hydrate (Mh) as an individual and/or in combination (CP-Mh) in hepatoma cells and tumor model. Exposure of CP resulted in the production of intracellular reactive oxygen species (ROS)-mediated cellular vacuolization, expansion of mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The remarkable suppression of adhesion and migration of SKOV-3 and A2780 cell lines together with the distinct regulation of autophagy and significant apoptotic induction was noticed after treatment with morin, although the exact autophagic mechanism of morin is still unknown (Nowak et al, 2020;Pal Singh et al, 2020). Autophagy activation has been implicated in cisplatin resistance, while autophagy suppression improves the effectiveness of morin in SKOV-3 cells (Bieg et al, 2018;Pal Singh et al, 2020). A study found that morin can induce melanoma cell apoptosis with ROS regulating pro and anti-apoptotic proteins (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable suppression of adhesion and migration of SKOV-3 and A2780 cell lines together with the distinct regulation of autophagy and significant apoptotic induction was noticed after treatment with morin, although the exact autophagic mechanism of morin is still unknown (Nowak et al, 2020;Pal Singh et al, 2020). Autophagy activation has been implicated in cisplatin resistance, while autophagy suppression improves the effectiveness of morin in SKOV-3 cells (Bieg et al, 2018;Pal Singh et al, 2020). A study found that morin can induce melanoma cell apoptosis with ROS regulating pro and anti-apoptotic proteins (Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We showed here that caspase-1 expression was higher in intermittent claudication, but undetectable in densely ischemic tissue affected by critical limb ischemia, which may also reflect similar state of cell exhaustion which is a hallmark of cellular senescence [ 36 ]. Another possible explanation for why HMGB1 release was reduced in ischemic cells is that its translocation is limited [ 37 ]. We showed very prominent nuclear HMGB1 staining in ischemic muscle affected by CLI, which would support this idea [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migration and proliferation of tumors can be suppressed by the natural compound morin (Nowak et al, 2020). Furthermore, this naturally occurring flavanol compound increased chemosensitivity via inhibition of autophagy (Pal Singh, Pal Khaket, et al, 2020). In prostate cancer cells, morin reduced miRNA‐155 expression to induce the expression of GATA binding protein 3 (GATA3), leading to PTX sensitivity (Li, Jin, et al, 2017).…”
Section: Micrornas and Paclitaxel Chemotherapymentioning
confidence: 99%